Hubungan Metode Persalinan Vacuum Ekstraksi dengan Kejadian Baby Blues Syndrome - Ledysta, Pupus; Soetrisno, .; Suwandono, Adji (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: extraction deliveries are significantly increases the risk of trauma and become a stressor for mothers. One of the risk factor is baby blues as if there are obstetric or deliveries complications, which are trauma factor plays an important role. This study aims to determine the relationship between the methods of vacuum extraction parturition with the baby blues syndrome incidence. Methods: the study was use observational analytic cross sectional approach. The observation was conducted at the inpatient clinic of the plant Obstetric and Gynecology Mawar 1 RSUD Dr. Moewardi Surakarta. The study sample involved 50 patients vaginal deliveries taken by purposive sampling fixed exposures method. Each sample was given an outline description of the study and asked to sign an informed consent sheet followed by charging sheets identity, L-MMPI questionnaire, and blues questionnaire. This study analyzed three independent variables, namely the method of delivery, age, and income. Data were analyzed by Chi Square test. Results: there was a statistically significant relationship between the methods of vacuum extraction delivery as a risk factor baby blues syndrome events. Maternal great risk with vacuum extraction deliveries to experience the baby blues syndrome incidence 6.08 times greater than women with spontaneous labor (0R = 6.08, IK 95% 1.72, 21.50, p = 0.004). Conclusion: based on research with vacuum extraction deliveries will have the risk of having a baby syndrome blues 6.08 times greater than spontaneous vaginal delivery. Keywords: vacuum extraction, baby blues syndromeÂ